ЁШЛАР ТАРБИЯСИДА ТАСВИРИЙ САНЪАТ АСАРЛАРИНИ БАДИИЙ ТАҲЛИЛ ҚИЛИШ АСОСЛАРИНИНГ ДОЛЗАРБ МАСАЛАЛАРИ - Қоржовов, Б.Ж. (SCIENCE and SOCIETY, 2020)
The article discusses the importance of the literary-artistic and scientific analysis of works of art in the education of the youth. The author also analyzed the work "Maternal Thoughts" by Rakhim Akhmedov and gave artistic, philosophical, logical conclusions and foundations.
Keywords: literary artistic analysis; creativity; inspiration; creative style; talent; art; scientific; character